(untitled) (Modern education and development, 2025)
Affixation a fundamental morphological process in English, involves adding prefixes and suffixes to root words, significantly impacting word formation, meaning, and grammatical function. This article examines the role of affixation in expanding vocabulary, changing word classes, and conveying nuanced meanings. We explore derivational and inflectional affixes, illustrating their importance in English linguistic structure. By analyzing scholarly perspectives,we highlight affixation’s contribution to language evolution and fluency.